MEMPERKUAT KOMPETENSI MULTIKULTURAL SISWA DALAM MENGHADAPI TANTANGAN GLOBAL - Sauqi Futaqi (MIDA : Jurnal Pendidikan Dasar Islam, 2021)
Global developments and problems force Islamic educational institutions to play their role, and this is a formidable challenge, especially in the economic and science and technology fields. However, in the midst of these formidable challenges, there are actually a number of potentials that can be developed. In addition to the historical advantages of the values and characteristics of Islamic education in Indonesia as a moderate Islamic education, at the same time it actually contains a spirit of progress. This spirit of progress can be seen from the value base of moderation which actually provides opportunities for progress. It's just a matter of how to manage these values and characteristics into a mainstay competency to give birth to various advantages. The study in this paper wants to conceptualize multicultural competencies which are considered to be one of the important competencies in facing global competition. In addition, this study also wants to emphasize that multicultural competence is not only understood in the context of social harmony, but must be developed into an Islamic education strategy in bringing about change and progress without destroying the human order. While multicultural competence can be understood as cultural and social capital for the success of Islamic education graduates, it can also be understood in terms of capital for the development of Islamic educational institutions in creating diverse and globally competitive advantages